PENCIPTAAN BUSANA ANAK DENGAN MENERAPKAN TEKNIK SUBSTRACTION CUTTING - Esther Mayliana (Institut Seni Indonesia Yogyakarta, 2019)
Children's clothing is clothing used by children in the age range of 6-12 years. Children's clothing has the main criteria that is comfortable when used. Comfort can be obtained from the choice of the type of material used and the design of children's clothing. The process of making fashion is very varied, and is increasingly developing, one of which is the Substraction cutting technique. Clothing made with substraction cutting techniques is usually women's clothing. This study wanted to examine the application of Substraction cutting techniques with the Tunnel method to make children's clothing.This study has 3 objectives, that is to find out how to make children's clothing with Substraction cutting techniques, efficient use of materials and speed of the fashion making process. This research uses the Action Reserch method. The method of creation through 3 stages, that is exploration, design and realization. In this study several techniques in pattern placement were carried out, and the results were: (1) Making clothes with the substraction cutting technique does not require two circle patterns to increase the volume, but just one circle pattern if needed., (2) Fabric folds when cutting material is necessary pay attention to produce the desired length of clothing, (3) The volume produced from the substraction cutting technique can be completed by draping technique, as decoration that is part of the children's clothing, (4) Substraction cutting technique removes relatively little fabric (5) The process that is passed is enough fast because it cuts down several stages in the process of making fashion in general.Keywords: Children's Clothing, Substraction Cutting, Tunnel Busana anak adalah busana yang digunakan oleh anak di rentang usia 6-12 tahun. Busana anak memiliki kriteria utama yaitu nyaman saat digunakan. Kenyamanan dapat diperoleh dari pilihan jenis bahan yang digunakan serta desain busana anak. Proses pembuatan busana sangat bervariasi, dan semakin berkembang, salah satunya adalah teknik Substraction cutting. Busana yang dibuat dengan teknik Substraction cutting biasanya adalah busana wanita. Penelitian kali ini ingin meneliti penerapan teknik Substraction cutting dengan metode Tunnel untuk membuat busana anak. Penelitian ini memiliki 3 tujuan, yaitu untuk mengetahui bagaimana cara membuat busana anak dengan teknik Substraction cutting, efisiensi penggunaan bahan dan kecepatan proses pembuatan busana. Penelitian ini menggunakan metode Action Reserch. Metode penciptaan melalui 3 tahapan yaitu eksplorasi, perancangan dan perwujudan. Pada penelitian ini beberapa tehnik dalam penempatan pola dilakukan, dan hasilnya adalah: (1) Pembuatan busana dengan teknik Substraction cutting tidak diperlukan dua pola lingkaran untuk penambah volume, namun cukup satu pola lingkaran jika diperlukan., (2) Lipatan kain saat memotong bahan perlu diperhatikan untuk menghasilkan panjang busana yang diinginkan, (3) Volume yang dihasilkan dari teknik Substraction cutting dapat diselesaikan dengan teknik draping, sebagai hiasan yang menjadi bagian dari busana anak, (4)Teknik Substraction cutting membuang kain relatif sedikit (5) Proses yang dilalui cukup cepat karena memangkas beberapa tahap dalam proses pembuatan busana pada umumnya.Kata kunci: Busana Anak, Substraction Cutting, Tunnel